Comparative effectiveness of screening strategies for colorectal cancer. Issue 9 (24th January 2017) - Barzi, Afsaneh; Lenz, Heinz‐Josef; Quinn, David I.; Sadeghi, Sarmad
Abstract : BACKGROUND: Screening for colorectal cancer (CRC) has been successful in decreasing the incidence and mortality from CRC. Although new screening tests have become available, their relative impact on CRC outcomes remains unexplored. This study compares the outcomes of various screening strategies on CRC outcomes. METHODS: A Markov model representing the natural history of CRC was built and validated against empiric data from screening trials as well as the Microstimulation Screening Analysis (MISCAN) model. Thirteen screening strategies based on colonoscopy, sigmoidoscopy, computed tomographic colonography, as well as fecal immunochemical, occult blood, and stool DNA testing were compared with no screening. A simulated sample of the US general population ages 50 to 75 years with an average risk of CRC was followed for up to 35 years or until death. Effectiveness was measured by discounted life years gained and the number of CRCs prevented. Discounted costs and cost‐effectiveness ratios were calculated. A discount rate of 3% was used in calculations. The study took a societal perspective. RESULTS: Colonoscopy emerged as the most effective screening strategy with the highest life years gained (0.022 life years) and CRCs prevented (n = 1068) and the lowest total costs ($2861). These values were 0.012 life years gained, 574 CRCs prevented, and a total cost of $3164, respectively, for FOBT; and 0.011 life years gained, 647 CRCs prevented, and a total cost of $4296, respectively, for DNA testing. Improved sensitivity or specificity of a screening test for CRC detection was not sufficient to close the outcomes gap compared with colonoscopy. CONCLUSIONS: Improvement in CRC‐detection performance is not sufficient to improve screening outcomes. Special attention must be directed to detecting precancerous adenomas. Cancer 2017;123:1516–1527. © 2017 American Cancer Society . Abstract : Colonoscopy remains the most effective screening tool for colorectal cancer. DNA stool testing, although interesting, is costlier and is not as effective as colonoscopy; the effectiveness gap cannot be closed by improving the sensitivity and specificity of DNA stool testing for colorectal cancer.